Narrativas Sobre Conflitos E Micropoderes Em Atos De Interpretação Simultânea De Língua Brasileira De Sinais No Contexto Escolar Bilíngue (PERcursos Linguísticos, 2020)
The study aims to analyze narratives of Brazilian Sign Language (Libras) Portuguese Translators-Interpreters (TILSP), in research interviews, focusing on the emergence of emic voices and the search for intelligibilities, in the perspective of Applied Linguistics (MOITA LOPES, 2006; KLEIMAN et. al., 2019). The theoretical-analytical basis is socio-interactional and studies of conflict narratives (BRIGGS, 1996; BRENNEIS, 1996), conducted with analyzes of the textualization of the Labovian narrative (LABOV, 1972). These are also important theoretical concepts: pragmatic knowledge (FAERCH, KASPER, 1984), in a socio-interactive model of communication (SCHFFRIN, 1986, 1994; PEREIRA, 2013); the microphysics of powers (FOUCAULT, 2015 [1978]; MACHADO, 2015), and micro-resistances (PINTO, FABRÍCIO, 2013), in conflicting interactions (SOUZA LEMOS, 2019). The methodology is qualitative and interpretive (DENZIN et. al., 2006), in an emic perspective (GARCEZ, 2008) and data generation in research interviews (ROUSTON, 2010). The transcriptions of the data were based on the conventions of the conversation analysis (SACKS et. al., 1974). The TILSP who was interviewed points out that there are linguistic disagreements and conflicts of knowledge expectations. The narrator also points out her micro resistance to the asymmetric power caused by the interference in the act of simultaneous interpretation in speech-in-interaction of the bilingual classroom.